Manufacturing method of multi-layer separator
By extruding, stretching and laminating the multi-layer diaphragm manufacturing method of different polyethylene and polypropylene compositions, the problems of multi-layer diaphragm structural unevenness and mechanical properties are solved, and efficient and economical thin-film diaphragm production is achieved.
Patent Information
- Application Number
- JP2024543864
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-27
- Filing Date
- 2022-11-07
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2042-11-07
AI Technical Summary
In the prior art, when manufacturing multi-layer diaphragms, the structural properties of each layer are uneven, resulting in unstable mechanical properties and poor production efficiency and economicality. The problems are more significant in thin film diaphragms (thickness less than 15 μm).
The first and second sheets are formed by extruding the first and second compositions containing different polyethylene and polypropylene respectively, stretching and laminating in the longitudinal and transverse directions, followed by removal of the pore forming agent to ensure structural uniformity of the layers and improve mechanical properties by thermal fixation and solvent extraction.
The structural uniformity and mechanical properties of thin-film multi-layer separators are achieved, while improving production efficiency and economy, and are suitable for lithium-ion batteries.
Smart Images

Figure 2025503935000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a multilayer separator, and more particularly to a method for producing a multilayer separator that can uniformize the structural properties of each layer constituting the multilayer separator and improve the mechanical properties required of the separator. [Background technology]
[0002] Lithium secondary batteries are widely used as power sources for various electrical products that require compactness and light weight, such as smartphones, laptops, and tablet PCs. As their application range expands to include smart grids and medium- to large-sized batteries for electric vehicles, there is a demand for the development of lithium secondary batteries with large capacity, long life, and high stability.
[0003] Recently, as the energy density of lithium secondary batteries has increased, the load on the batteries has increased, and a high level of safety is also required for separators. This has highlighted the importance of not only the mechanical properties of the separator, but also its heat resistance, which can ensure safety.
[0004] Polyolefin-based microporous membranes have been used as separators for lithium secondary batteries. Among polyolefin-based microporous membranes, microporous membranes made of polyethylene resins in particular are known to have an excellent shutdown function in which the micropores of the porous membrane are blocked to cut off the flow of current when the temperature of the battery rises. However, the battery temperature may rise further after the shutdown function is activated. In this case, the meltdown of the separator progresses, causing a short circuit inside the battery, which generates a large amount of heat and may cause dangers such as smoke, fire, and explosion. Therefore, it is necessary to suppress the risk of a short circuit even at temperatures higher than the shutdown temperature.
[0005] In order to achieve both shutdown and meltdown properties in a separator, methods have been proposed in which polyethylene and polypropylene are blended, or a microporous membrane made of a polyethylene resin is laminated with a microporous membrane made of a polypropylene resin.
[0006] For example, Patent Documents 1 and 2 disclose a method for manufacturing a multi-layer separator by co-extrusion of two or more resin compositions, and disclose that the mechanical strength and heat resistance of the multi-layer separator manufactured through this method can be improved in a balanced manner. However, since interlayer lamination is performed by co-extrusion before the pore structure is formed by stretching, that is, lamination is performed, there is a problem that the structural properties of each layer become non-uniform in the subsequent film-forming process such as stretching and extraction. Specifically, as the thickness deviation of each region of the outermost layer of the multi-layer separator increases, the mechanical properties of the separator itself may become non-uniform, and in particular, when assembling a battery using the separator, there is a problem that the part that is significantly thinner than the surrounding region is easily damaged or broken. This problem is more prominent in thin-film separators (thickness of about 15 μm or less, preferably about 10 μm or less) to meet the recent trend of battery integration and high capacity.
[0007] Patent Document 3 discloses a method for manufacturing a multi-layer separator by laminating and stacking two or more separators that have been completely formed through extrusion, stretching, extraction, and heat setting, as shown in Fig. 1. However, in this case, since sufficient interlayer bonding strength cannot be imparted, there is a problem that each layer easily peels off. To improve this, a process of laminating two or more separators and then re-stretching and heat setting can be added, but there is a problem that the productivity and economy are reduced due to the added equipment and process. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2005-0120689 [Patent Document 2] Korean Patent Publication No. 10-2016-0094448 [Patent Document 3] Korean Patent Publication No. 10-2008-0028444 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made to solve the problems of the prior art as described above, and an object of the present invention is to provide a method for producing a thin-film multilayer separator having a thickness of about 15 μm or less, preferably about 10 μm or less, which can uniformize the structural properties of each layer constituting the multilayer separator, stably ensure the mechanical properties required of the separator, and at the same time, improve productivity and cost-effectiveness. [Means for solving the problem]
[0010] One aspect of the present invention provides a method for producing a multilayer separator, comprising: (a) extruding a first composition comprising a first polyolefin and a first pore-former to produce a first sheet; (b) extruding a second composition comprising a second polyolefin and a second pore-former to produce a second sheet; (c) stretching the first and second sheets in a machine direction (MD) to produce first and second precursor films, respectively; (d) laminating the first and second precursor films to obtain a laminate; and (e) stretching the laminate in a transverse direction (TD), and then removing the first and second pore-formers from the laminate.
[0011] In one embodiment, the first and second polyolefins may each comprise one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, and combinations or copolymers of two or more thereof.
[0012] In one embodiment, the first and second polyolefins may each have a weight average molecular weight of 300,000 to 2,000,000. In one embodiment, the first and second pore forming agents may each be paraffin oil having a kinematic viscosity at 40° C. of 50 to 100 cSt.
[0013] In one embodiment, the first or second composition may further comprise a hydrophilic polymer. In one embodiment, the content of the hydrophilic polymer in the first or second composition may be 0.1 to 5% by weight.
[0014] In one embodiment, the hydrophilic polymer may be one selected from the group consisting of ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl alcohol, polyacrylic acid, polyoxyethylene-polyoxypropylene block copolymer, polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, polyvinyl acetal, polyvinyl butyral, cellulose derivatives, glycerol, and combinations of two or more thereof.
[0015] In one embodiment, the first and second precursor films may be pressed against each other during lamination, so that at least a portion of the interface between the first and second precursor films may be adhered to each other.
[0016] Another aspect of the present invention provides a multi-layer separator produced by the above production method, wherein the thickness deviation of the outermost layer, as measured by the following formula, is 10% or less. <expression> Thickness deviation (%) = {(maximum thickness) - (minimum thickness)} / (minimum thickness) x 100
[0017] In the above formula, the thickness deviation is determined by a method including the steps of: cutting the multilayer separator to 100 mm x 100 mm (MD x TD), then dividing it into 5 equal parts in the machine direction (MD) to obtain 5 test pieces each having a size of 20 mm x 100 mm (MD x TD); measuring the thickness of the outermost layer at the center of the test pieces in the machine direction (TD); and calculating the thickness deviation by the formula based on the maximum and minimum values of the thickness.
[0018] In one embodiment, the multilayer separator can satisfy at least one of the following conditions (i) to (vi).
[0019] (i) thickness 1 to 15 μm, (ii) puncture strength 600 gf or more, (iii) machine direction (MD) tensile strength 1,300 to 2,000 kgf / cm 2 (iv) Transverse (TD) tensile strength: 3,000 to 6,000 kgf / cm 2 , (v) machine direction (MD) tensile elongation of 150-450%, and (vi) transverse direction (TD) tensile elongation of 30-100%. Effect of the Invention
[0020] A method for producing a multilayer separator according to one embodiment of the present invention includes the steps of: (a) extruding a first composition containing a first polyolefin and a first pore-forming agent to produce a first sheet; (b) extruding a second composition containing a second polyolefin and a second pore-forming agent to produce a second sheet; (c) stretching the first and second sheets in the machine direction (MD) to produce first and second precursor films, respectively; (d) laminating the first and second precursor films to obtain a laminate; and (e) stretching the laminate in the transverse direction (TD) and then removing the first and second pore-forming agents from the laminate. This makes it possible to uniformize the structural properties of each layer constituting the multilayer separator and stably ensure the mechanical properties required for the separator while improving productivity and economy when producing a thin-film multilayer separator having a thickness of about 15 μm or less, preferably about 10 μm or less.
[0021] It should be understood that the effects of the present invention are not limited to the effects described above, but include all effects that can be inferred from the configuration of the invention described in the detailed description of the present invention or the claims. [Brief description of the drawings]
[0022] [Figure 1] 1 shows a method for manufacturing a multi-layer separator according to the prior art. [Diagram 2] 1 illustrates a method for making a multi-layer separator according to one embodiment of the present invention. [Diagram 3] 1 illustrates a method for measuring thickness deviation of a multi-layer separator according to one embodiment of the present invention. [Figure 4] 4 illustrates a method for manufacturing a multi-layer separator according to a comparative example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be described below. However, the present invention can be realized in various different forms and is not limited to the embodiments described herein. In addition, in order to clearly explain the present invention in the drawings, parts that are not related to the description are omitted, and similar parts are given similar reference numerals throughout the specification.
[0024] Throughout the specification, when any part is said to be "connected" to another part, this includes not only the case where it is "directly connected" to another part, but also the case where it is "indirectly connected" through another member in between. Furthermore, when any part is said to "include" a certain component, this does not mean that it excludes the other component, but that it may further include the other component, unless otherwise specified to the contrary. Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0025] Figure 2 shows a method for producing a multi-layer separator according to one embodiment of the present invention. Referring to Figure 2, the method for producing a multi-layer separator according to one embodiment of the present invention may include: (a) extruding a first composition comprising a first polyolefin and a first pore former to produce a first sheet; (b) extruding a second composition comprising a second polyolefin and a second pore former to produce a second sheet; (c) stretching the first and second sheets in the machine direction (MD) to produce first and second precursor films, respectively; (d) laminating the first and second precursor films to obtain a laminate; and (e) stretching the laminate in the transverse direction (TD), and then removing the first and second pore formers from the laminate.
[0026] In the steps (a) and (b), the first and second compositions having the same or different compositions can be extruded independently to produce the first and second sheets. The extrusion can be carried out using two independent extruders (first and second extruders) arranged in parallel to each other. The structure, configuration, specifications, capacity, etc. of the first and second extruders can be the same, and the first and second extruders can be designed differently as necessary to optimize the composition and physical properties of the first and second compositions, and thus the physical properties of each layer constituting the multi-layer separator. The first and second compositions can be melted and kneaded in the first and second extruders, and can be discharged at a predetermined thickness through a device or equipment such as a T-die installed downstream of the first and second extruders to produce the first and second sheets.
[0027] The first and second polyolefins may each include, but are not limited to, one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, and combinations or copolymers of two or more thereof, preferably polyethylene and / or polypropylene, and more preferably polyethylene.
[0028] The weight average molecular weight of each of the first and second polyolefins may be 300,000 to 2,000,000, and the molecular weight distribution (Mw / Mn) may be 3 to 7. The first and second polyolefins may be the same type and / or of the same quality, or may be different types and / or of different qualities, as necessary. If the molecular weight distribution of the first and second polyolefins is less than 3, the dispersibility with the first and second pore-forming agents may decrease, and the uniformity of the manufactured multi-layer separator may decrease, and if it is more than 7, the mechanical properties of the multi-layer separator may decrease.
[0029] When the first and second polyolefins are different, the first polyolefin may be a high density polyethylene (HDPE) having a weight average molecular weight of 300,000 to 800,000, and the second polyolefin may be an ultra-high molecular weight polyethylene (UHMWPE) having a weight average molecular weight of 1,000,000 to 2,000,000. In general, the high density polyethylene can contribute to the mechanical properties such as tensile strength, tensile elongation, and puncture strength of the separator, and the ultra-high molecular weight polyethylene can contribute to the heat resistance of the separator, so that the mechanical properties and heat resistance of the separator can be complemented by the combination of the two, but these effects are not necessarily complementary to each other, and in some cases, the mechanical properties and / or heat resistance can be further improved.
[0030] The ratio of the weight average molecular weight of the second polyolefin to the weight average molecular weight of the first polyolefin may be 0.5 to 2, preferably 0.65 to 1.5. If the ratio is less than 0.5 or more than 2, the deviation of the structure, mechanical properties and / or heat resistance of the layers derived from the first and second compositions in the multilayer separator may fall outside the allowable range, and compatibility with the battery may decrease.
[0031] The first and second pore forming agents may each be paraffin oil having a kinetic viscosity of 50 to 100 cSt at 40°C. The first and second pore forming agents may be of the same type and / or of the same quality, or may be of different types and / or of different qualities, as necessary. If the kinetic viscosity of the first and second pore forming agents at 40°C is out of the above range, the viscosity of the first and second compositions may be too low or too high, so that the processability and dispersibility may be reduced. In addition to the paraffin oil, the first and second pore forming agents may each be one selected from the group consisting of paraffin wax, mineral oil, solid paraffin, soybean oil, rapeseed oil, palm oil, coconut oil, di-2-ethylhexyl phthalate, dibutyl phthalate, diisononyl phthalate, diisodecyl phthalate, bis(2-propylheptyl) phthalate, naphthenic oil, and a combination of two or more of these, but are not limited thereto. The first and second compositions may each comprise 20-50% by weight of the first and second polyolefins and 50-80% by weight of the pore-forming agent.
[0032] The first or second composition may further include a hydrophilic polymer. A separator consisting of only the first and second polyolefins is essentially hydrophobic, but a predetermined hydrophilicity can be imparted to the separator by melting and kneading a certain amount of hydrophilic polymer with the polyolefin during the manufacture of the separator. In this case, the molecular weight of the polyolefin and the content of the hydrophilic polymer in the separator are optimized to derive and combine variables that realize a required level of electrolyte impregnation, thereby achieving a balanced productivity of the process for melting and kneading the hydrophilic polymer with the polyolefin, the hydrophilicity of the separator, and the resulting electrolyte impregnation.
[0033] The layer of the multilayer separator further containing the hydrophilic polymer may have a hydrophobic region containing the polyolefin and a hydrophilic region containing the hydrophilic polymer dispersed in the hydrophobic region. The content of the hydrophilic region in the layer may be 0.1 to 7.5% by weight, which can be achieved by adjusting the content of the hydrophilic polymer in the first or second composition to the range of 0.1 to 5% by weight.
[0034] In the layer, the hydrophobic region made of the first or second polyolefin and the hydrophilic region made of the hydrophilic polymer may constitute a continuous phase and a discontinuous phase, respectively. In the layer, the hydrophilic region is uniformly dispersed in a matrix made of the hydrophobic region, and can impart substantially uniform hydrophilicity to the entire area and / or thickness direction of the layer, thereby improving the impregnation of the layer with the electrolyte. The term "matrix" used in this specification means a component that constitutes a continuous phase in a layer or separator containing two or more components. That is, in the layer, the hydrophobic region containing the polyolefin may exist as a continuous phase, and the hydrophobic region containing the hydrophilic polymer may exist dispersedly in the continuous phase.
[0035] The content of the hydrophilic region in the layer may be 0.1 to 7.5% by weight, preferably 1 to 6% by weight, and more preferably 3 to 6% by weight. If the content of the hydrophilic region is 0.1% by weight, the required level of electrolyte impregnation cannot be achieved, and if it is more than 7.5% by weight, the electrolyte impregnation can be further improved, but the mechanical properties and heat resistance of the separator that can be achieved through the polyolefin may be reduced. In addition, if the content of the hydrophilic region is more than 7.5% by weight, the dispersibility of the hydrophilic polymer decreases, the number of surface defects having a different brightness from the surrounding area on the surface of the layer and a size of 2 mm or more increases, and the appearance quality may be reduced, and the resistance may suddenly change at the site and / or region where the hydrophilic polymer randomly aggregates on the surface and / or inside of the layer, which may adversely affect the electrochemical properties of the battery.
[0036] When the first or second polyolefin to be mixed with the hydrophilic polymer is a high density polyethylene (HDPE), the weight average molecular weight of the polyethylene may be 200,000 to 800,000, preferably 250,000 to 600,000, and more preferably 300,000 to 500,000, and the ratio of the content of the hydrophilic region to the weight average molecular weight of the high density polyethylene is 0.1 × 10 -5 ~1.1×10 -5 , preferably 0.2 x 10 -5 ~1×10 -5 , more preferably 0.5×10 -5 ~1×10 -5 may be also possible.
[0037] The ratio of the content of the hydrophilic region to the weight average molecular weight of the high-density polyethylene is 0.1×10 -5 If the thickness is less than 1.1×10, the required level of electrolyte impregnation cannot be achieved. -5 If the ratio is larger than 1.1×10, the electrolyte impregnation property is decreased, and the mechanical properties and heat resistance of the separator that can be realized by the high density polyethylene are decreased. -5 If it is larger, the dispersibility of the hydrophilic polymer decreases, the number of surface defects having a different brightness from the surrounding area and a size of 2 mm or more increases on the surface of the separator, and the appearance quality may decrease. Also, the resistance may suddenly change at sites and / or regions where the hydrophilic polymer randomly aggregates on the surface and / or inside of the separator, which may adversely affect the electrochemical properties of the battery.
[0038] In addition, when the first or second polyolefin to be mixed with the hydrophilic polymer is ultra-high molecular weight polyethylene (UHMWPE), the weight average molecular weight of the polyethylene may be 1,000,000 to 2,000,000, preferably 1,000,000 to 1,500,000, and the ratio of the content of the hydrophilic region to the weight average molecular weight of the ultra-high molecular weight polyethylene is 0.1 × 10 -5 ~0.75×10 -5 , preferably 0.15 x 10 -5 ~0.6×10 -5 , and more preferably 0.3×10 -5 ~0.6×10 -5 may be also possible.
[0039] The ratio of the content of the hydrophilic region to the weight average molecular weight of the ultra-high molecular weight polyethylene is 0.1×10 -5 If the thickness is less than 0.75×10, the required level of electrolyte impregnation cannot be achieved. -5 If the ratio is larger than 0.75×10, the electrolyte impregnation property is decreased, and the mechanical properties and heat resistance of the separator that can be realized by the ultra-high molecular weight polyethylene are decreased. -5 If it is larger, the dispersibility of the hydrophilic polymer will decrease, the number of surface defects having a different brightness from the surrounding area on the surface of the layer and a size of 2 mm or more will increase, and the appearance quality will decrease. Also, the resistance will suddenly change at sites and / or areas where the hydrophilic polymer randomly aggregates on the surface and / or inside of the layer, which may adversely affect the electrochemical properties of the battery.
[0040] The hydrophilic polymer may be one selected from the group consisting of ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl alcohol, polyacrylic acid, polyoxyethylene-polyoxypropylene block copolymer, polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, polyvinyl acetal, polyvinyl butyral, cellulose derivatives, glycerol, and a combination of two or more of these, preferably ethylene vinyl acetate, more preferably ethylene vinyl acetate with a vinyl acetate content of 15 to 30% by weight, but is not limited thereto. If the vinyl acetate content of ethylene vinyl acetate is less than 15% by weight, the mechanical properties and hydrophilicity of the separator may decrease, and if it is more than 30% by weight, the processability and the dispersibility of the hydrophilic polymer may decrease. In addition to the above-mentioned hydrophilic polymers, various types of polymers having hydrophilic functional groups such as amine groups, amide groups, hydroxyl groups, and carboxylic acid groups in the main chain and / or side chains may also be applied as the hydrophilic polymer.
[0041] Among the hydrophilic polymers, the ethylene vinyl acetate not only imparts soft properties, i.e., a certain degree of flexibility, to the first and second polyolefins and improves the tensile elongation of each layer derived from the first and second compositions and the multilayer separator including the same, but also increases the interlayer bonding strength of each layer constituting the multilayer separator, thereby contributing to improving mechanical properties such as puncture strength.
[0042] In the step (c), the first and second sheets can be stretched in the machine direction (MD) to produce first and second precursor films. The machine direction (MD) stretching of the first and second sheets can be performed using a first and a second stretching machine installed downstream of the first and the second extruder, respectively.
[0043] The first and second stretching machines are devices for stretching the first and second sheets discharged from the first and second extruders, respectively, along the transport direction of the first and second sheets in the process line, and the stretching direction of the first and second sheets by the first and second stretching machines can be defined as a machine direction (MD, mechanical direction). The first and second stretching machines may each be a roll stretching machine. The roll stretching machine includes a plurality of rolls along the transport direction of the sheet, and can stretch the sheet at a predetermined ratio along the machine direction (MD) by rotating a roll located at a rear stage faster than a roll located at a front stage. The stretching ratios of the first and second sheets may each be 2 to 20 times, preferably 5 to 10 times. The stretching ratios of the first and second sheets may be the same or different, and preferably, these stretching ratios can be set to be the same in consideration of the adhesive strength of the first and second precursor films manufactured in the (c) process and the interlayer bonding strength resulting therefrom, but are not limited thereto.
[0044] In the step (d), the first and second precursor films are laminated to obtain a laminate. The lamination can be performed by a predetermined laminator. The laminator is a facility or device that laminates the first and second precursor films manufactured by the first and second stretching machines to each other. During the lamination, the first and second precursor films are pressed to face each other, and at least a part, preferably the entirety of the interface between the first and second precursor films can be adhered. The adhesion can be performed by a physical means such as heat, ultrasonic waves, high frequency waves, and lasers that are applied to at least a part, preferably the entirety of the surface of the first and second precursor films, and the running stability of the laminate passing through facilities or devices for subsequent stretching (TD), extraction, and heat fixing can be improved through the adhesion, and thus structural non-uniformity that appears in the outermost layer of a conventional multilayer separator, such as excessive deviation in the thickness, porosity, etc. of the outermost layer, can be effectively eliminated.
[0045] In the step (e), the first and second pore-forming agents can be removed from the laminate after the laminate is stretched in the transverse direction (TD). The transverse direction (TD) stretching of the laminate can be performed by a third stretching machine.
[0046] The third stretching machine may stretch the laminate in a transverse direction (TD). The third stretching machine may be a tenter stretching machine. The tenter stretching machine may stretch the laminate at a predetermined stretch ratio by fixing both ends of the laminate in the transverse direction with a predetermined member such as a chuck or clip and separating the member in the transverse direction. The transverse direction (TD) stretch ratio of the laminate by the third stretching machine may be 2 to 20 times, preferably 5 to 10 times, but is not limited thereto.
[0047] Then, a predetermined extraction solvent is applied to the laminate, and the first and second pore-forming agents can be simultaneously and selectively extracted and removed from the laminate, specifically, from the first and second precursor films constituting the laminate. The first and second pore-forming agents can be extracted and removed by immersing the laminate in an impregnation tank carrying a solution containing the extraction solvent for a predetermined time.
[0048] After extraction, the content of the pore-forming agent remaining on the surface and / or inside of the laminate may be 1 wt % or less. The extraction solvent may be, for example, methyl ethyl ketone, hexane, dichloromethane, etc., but is not limited thereto. The time required for extracting and removing the first and second pore-forming agents can be determined depending on the thickness and porosity of the laminate, and may be 10 minutes or less, preferably 5 minutes or less, when the thickness and porosity of the laminate are 1 to 15 μm and 40 to 70 vol %, respectively.
[0049] In addition, the laminate from which the first and second pore-forming agents have been extracted and removed may be heated to remove the extraction solvent remaining in the laminate. A portion of the extraction solvent applied in step (e) may remain on the surface and / or inside of the laminate. The remaining extraction solvent may deteriorate the properties of the subsequent process and the separator manufactured therethrough, so the extraction solvent remaining in the laminate may be removed by appropriately heating the laminate at a temperature equal to or higher than the boiling point of the extraction solvent.
[0050] The method for producing the multilayer separator may further include a step (e') of heat fixing the laminate after the step (e). The heat fixing refers to a step of applying heat to the laminate in a fixed state to forcibly fix the laminate that is about to shrink and remove residual stress. A high heat fixing temperature is advantageous for reducing the shrinkage rate, but if the temperature is too high, the laminate may partially melt, closing the formed pores and reducing the permeability.
[0051] The heat setting temperature is preferably selected within a range in which 10 to 30% by weight of the crystalline portion of the laminate melts. When the heat setting temperature is selected within the range, it is possible to prevent the problem of insufficient rearrangement of the polyolefin molecules in the laminate, resulting in no effect of removing residual stress in the film, and the problem of partial melting causing pore closure and reduced transmittance. For example, the heat setting temperature may be 120 to 140°C, preferably 123 to 135°C, and the heat setting time may be 5 seconds to 1 minute.
[0052] Another aspect of the present invention provides a multilayer separator produced by the above-mentioned production method, wherein the thickness deviation of the outermost layer, as measured by the following formula, is 10% or less, preferably 1 to 8.5%, or 3 to 6.5%. <expression> Thickness deviation (%) = {(maximum thickness) - (minimum thickness)} / (minimum thickness) x 100
[0053] Conventionally, in the manufacturing method of a multilayer separator, interlayer lamination is performed by co-extrusion before the pore structure is formed by stretching, i.e., lamination may be performed, which causes a problem that the structural properties of each layer become non-uniform in the subsequent film-forming process such as stretching and extraction. Specifically, as the thickness deviation in each region of the outermost layer of the multilayer separator increases, the mechanical properties of the multilayer separator itself may become non-uniform, and in particular, when assembling a battery using the multilayer separator, the portion that is significantly thinner than the surrounding region is easily damaged or broken. This problem is more prominent in thin-film separators (thickness of about 15 μm or less, preferably about 10 μm or less) that are used to meet the recent trend of battery integration and high capacity.
[0054] In contrast, the multilayer separator is manufactured by laminating the first and second precursor films, which have been stretched in the machine direction (MD) to form a predetermined pore structure, and then stretching the laminate in the transverse direction (TD) to obtain a laminate, and then extracting and removing the first and second pore-forming agents. This makes it possible to uniformize the structural properties of each layer constituting the multilayer separator and ensure stable mechanical properties, while minimizing the number of stretching machines required to manufacture the multilayer separator, thereby improving productivity and economy.
[0055] 3 shows a method for measuring the thickness deviation of a multi-layer separator according to an embodiment of the present invention. Referring to FIG. 3, the thickness deviation of the outermost layer can be calculated using the thickness of each test piece measured by the following method and the above formula. In the above formula, the thickness deviation is determined by a method including the steps of: cutting the multi-layer separator to 100 mm×100 mm (MD×TD), then dividing it into 5 equal parts in the machine direction (MD) to obtain 5 test pieces each having a size of 20 mm×100 mm (MD×TD); measuring the thickness of the outermost layer at the center of the test pieces in the machine direction (TD); and calculating the thickness deviation according to the above formula based on the maximum and minimum values of the thickness.
[0056] Moreover, the multilayer separator can satisfy at least one, and preferably all, of the following conditions (i) to (vi).
[0057] (i) a thickness of 1 to 15 μm, preferably 5 to 12 μm; (ii) a puncture strength of 600 gf or more, preferably 700 to 1,000 gf, more preferably 750 to 900 gf; (iii) a machine direction (MD) tensile strength of 1,300 to 2,000 kgf / cm 2 , preferably 1,400 to 1,800 kgf / cm 2 (iv) Transverse (TD) tensile strength: 3,000 to 6,000 kgf / cm 2 , preferably 3,500 to 5,500 kgf / cm 2 , and more preferably 4,000 to 5,400 kgf / cm 2 , (v) machine direction (MD) tensile elongation of 150-450%, preferably 200-400%, more preferably 230-350%, and (vi) transverse direction (TD) tensile elongation of 30-100%, preferably 40-90%. Hereinafter, embodiments of the present invention will be described in detail.
[0058] Example 1 A first composition obtained by mixing 28 parts by weight of high density polyethylene (HDPE) having a weight average molecular weight of 600,000 and 72 parts by weight of paraffin oil having a kinetic viscosity of 70 cSt at 40°C was fed into a twin-screw extruder (first extruder, inner diameter 58 mm, L / D=56). The first composition was discharged from a T-die having a width of 400 mm under conditions of a screw rotation speed of 120 rpm and a temperature of 210°C, and then passed through a casting roll at a temperature of 70°C to produce a first sheet having a thickness of 800 μm.
[0059] The second composition, which was the same as the first composition, was fed into a twin-screw extruder (second extruder, inner diameter 58 mm, L / D=56) that had the same configuration as the first extruder and was arranged in parallel. The second composition was extruded from a T-die with a width of 400 mm under conditions of a screw rotation speed of 120 rpm and a temperature of 210° C., and then passed through a casting roll at a temperature of 70° C. to produce a second sheet with a thickness of 800 μm.
[0060] The first and second sheets were fed into first and second stretching machines (roll stretching machines) arranged in parallel to each other, and stretched 8 times in the machine direction (MD) at 120° C. to produce first and second precursor films. Here, the first and second stretching machines refer to stretching machines provided in the subsequent stages of the first and second extruders, respectively.
[0061] The first and second precursor films were fed into a laminator installed downstream of the first and second stretching machines, and the first and second precursor films were laminated in contact with each other to obtain a laminate.
[0062] The laminate was placed in a third stretching machine (tenter stretching machine) and stretched 9 times in the transverse direction (TD) at 126° C., then immersed in a dichloromethane leaching tank at 25° C. for 1 minute to extract and remove the paraffin oil, and dried for 5 minutes at 38° C. The laminate was stretched 1.5 times in the transverse direction (TD) at 138° C., then relaxed by 10% and heat-set to obtain a separator.
[0063] Example 2 A separator was manufactured in the same manner as in Example 1, except that the high density polyethylene (HDPE) having a weight average molecular weight of 600,000 in the second composition was replaced with an ultra high molecular weight polyethylene (UHMWPE) having a weight average molecular weight of 1,000,000.
[0064] Example 3 A separator was manufactured in the same manner as in Example 1, except that the second composition further contained ethylene vinyl acetate (EVA, HTC Corp.) with a vinyl acetate content of 28% by weight, and the contents (parts by weight) of the high-density polyethylene, ethylene vinyl acetate, and paraffin oil in the second composition were changed to 30.4 parts by weight, 1.6 parts by weight, and 68.0 parts by weight, respectively.
[0065] Example 4 A separator was manufactured in the same manner as in Example 3, except that the high density polyethylene (HDPE) having a weight average molecular weight of 600,000 in the second composition was replaced with an ultra high molecular weight polyethylene (UHMWPE) having a weight average molecular weight of 1,000,000.
[0066] Example 5 A separator was manufactured in the same manner as in Example 1, except that an ultrasonic wave of 50 kHz was applied to the entire surface of the laminate during lamination to bond (fuse) the interface of the laminate.
[0067] Example 6 A separator was manufactured in the same manner as in Example 2, except that an ultrasonic wave of 50 kHz was applied to the entire surface of the laminate during lamination to bond (fuse) the interface of the laminate.
[0068] Example 7 A separator was manufactured in the same manner as in Example 3, except that an ultrasonic wave of 50 kHz was applied to the entire surface of the laminate during lamination to bond (fuse) the interface of the laminate.
[0069] Example 8 A separator was manufactured in the same manner as in Example 4, except that an ultrasonic wave of 50 kHz was applied to the entire surface of the laminate during lamination to bond (fuse) the interface of the laminate.
[0070] Comparative Example 1 25 parts by weight of a mixture containing 60% by weight of ultra-high molecular weight polyethylene having a weight average molecular weight of 2,000,000 and 40% by weight of high density polyethylene having a weight average molecular weight of 560,000, and 75 parts by weight of paraffin oil having a kinetic viscosity of 35 cSt at 40°C were charged into a twin-screw extruder (first extruder, inner diameter 58 mm, L / D = 56) and melt-kneaded under conditions of a screw rotation speed of 250 rpm and 230°C to produce a first polyolefin solution.
[0071] 30 parts by weight of a mixture containing 50% by weight of high-density polyethylene having a weight-average molecular weight of 560,000 and 50% by weight of polypropylene having a weight-average molecular weight of 1,600,000, and 70 parts by weight of paraffin oil having a kinetic viscosity of 35 cSt at 40°C were fed into a twin-screw extruder (second extruder, inner diameter 58 mm, L / D=56) having the same configuration as the first extruder and arranged in parallel, and melt-kneaded under the same conditions to produce a second polyolefin solution.
[0072] The first and second polyolefin solutions were fed from the first and second extruders to a three-layer T-die, respectively, and extruded so that the layer thickness ratio of the first / second / first polyolefin solutions was 35 / 30 / 35. The extrusion molded body was taken up and cooled by a cooling roll (diameter 500 mm) at 37°C to produce a gel-like three-layer sheet. The gel-like three-layer sheet was simultaneously biaxially stretched 5x5 times (MDxTD) at 114°C, and then immersed in a dichloromethane leaching tank at 25°C for 5 minutes to extract and remove paraffin oil, thereby producing a porous membrane. The porous membrane was placed in a tenter stretching machine, re-stretched 1.4 times in the transverse direction (TD) at 124°C, and then heat-set to produce a separator.
[0073] Comparative Example 2 29.5 parts by weight of high density polyethylene having a weight average molecular weight (Mw) of 350,000, 0.5 parts by weight of silane-modified high density polyethylene, and 70 parts by weight of paraffin oil having a kinetic viscosity of 70 cSt at 40°C were mixed and fed into a twin-screw extruder (inner diameter 58 mm, L / D=56). Dibutyltin laurate, a crosslinking catalyst, was dispersed in advance in a portion of the paraffin oil and fed through a side injector of the twin-screw extruder so that the content was 0.5% by weight based on the total weight of the material passing through the twin-screw extruder. The mixture was discharged from the twin-screw extruder through a T-die having a width of 300 mm under conditions of a screw rotation speed of 40 rpm and 200°C, and then passed through a cast roll at a temperature of 40°C to produce a base sheet having a thickness of 800 μm.
[0074] The base sheet was stretched 6 times in the machine direction (MD) using a roll stretching machine at 110 ° C., and stretched 7 times in the transverse direction (TD) using a tenter stretching machine at 125 ° C. to produce a film. The film was immersed in a dichloromethane leaching tank at 25 ° C., paraffin oil was extracted and removed for 1 minute, and then dried at 50 ° C. for 5 minutes to produce a porous film. Then, after heating at 125 ° C. using a tenter stretching machine, it was stretched 1.45 times in the transverse direction (TD) and relaxed, and heat-set to 1.25 times compared to before stretching. The film was crosslinked for 72 hours in a constant temperature and humidity tank at 85 ° C. and 85% humidity to produce a separator.
[0075] Comparative Example 3 30 parts by weight of a mixture containing 64% by weight of ultra-high molecular weight polyethylene (UHMWPE) having a weight average molecular weight (Mw) of 1,000,000 and 36% by weight of ultra-high molecular weight polyethylene (UHMWPE) having a weight average molecular weight (Mw) of 1,500,000, and 70 parts by weight of paraffin oil having a kinetic viscosity of 70 cSt at 40°C were mixed and fed into a twin-screw extruder (inner diameter 58 mm, L / D = 56). The mixture was discharged from the twin-screw extruder through a T-die having a width of 300 mm under conditions of a screw rotation speed of 40 rpm and 200°C, and then passed through a casting roll at a temperature of 40°C to produce a base sheet having a thickness of 800 μm.
[0076] The base sheet was stretched 6 times in the machine direction (MD) using a roll stretching machine at 110°C, and stretched 7 times in the transverse direction (TD) using a tenter stretching machine at 125°C to produce a film. The film was immersed in a dichloromethane leaching tank at 25°C for 1 minute to extract and remove paraffin oil, and dried at 50°C for 5 minutes to produce a porous film. Thereafter, the film was heated at 125°C using a tenter stretching machine, stretched 1.45 times in the transverse direction (TD), relaxed, and heat-set to 1.25 times the size before stretching to produce a separator.
[0077] Comparative Example 4 A separator was manufactured in the same manner as in Comparative Example 3, except that 30 parts by weight of a mixture containing 42% by weight of high density polyethylene (HDPE) having a weight average molecular weight (Mw) of 600,000 and 58% by weight of ultra high molecular weight polyethylene (UHMWPE) having a weight average molecular weight (Mw) of 1,500,000 and 70 parts by weight of paraffin oil having a kinetic viscosity of 70 cSt at 40°C were mixed and fed into a twin-screw extruder (inner diameter 58 mm, L / D = 56).
[0078] Comparative Example 5 100 parts by weight of a mixture containing 90% by weight of ultra-high molecular weight polyethylene (UHMWPE) having a weight average molecular weight of 1,000,000 and 10% by weight of high density polyethylene (HDPE) having a weight average molecular weight of 380,000 was fed into a twin-screw extruder (first extruder, inner diameter 58 mm, L / D=42). 250 parts by weight of paraffin oil was fed through a side injector of the first extruder, and melt-kneaded under conditions of 210°C and 100 rpm to produce a first polyethylene solution.
[0079] 100 parts by weight of a mixture containing 10% by weight of ultra-high molecular weight polyethylene (UHMWPE) having a weight average molecular weight of 1,000,000 and 90% by weight of high density polyethylene (HDPE) having a weight average molecular weight of 380,000 was fed into a twin-screw extruder (second extruder, inner diameter 58 mm, L / D=42). 250 parts by weight of paraffin oil was fed through a side injector of the second extruder, and melt-kneaded under conditions of 210°C and 100 rpm to produce a second polyethylene solution.
[0080] The first and second polyethylene solutions were passed through a multiblock (multilayering device) of an extruder to alternately layer the first and second polyethylene solutions, and then extruded through a T-die to form a multilayer structure consisting of 20 layers.
[0081] The multilayer structure was passed through a cooling roll adjusted to 40° C. to produce a gel-like base sheet with a thickness of 1,100 μm. The base sheet was simultaneously biaxially stretched 8×8 times (MD×TD) at 124° C., then immersed in a dichloromethane leaching tank at 25° C. for 10 minutes to extract and remove paraffin oil, and dried at 50° C. for 5 minutes to produce a porous membrane. The porous membrane was placed in a tenter stretching machine, stretched again in the transverse direction (TD) by 1.4 times at 125° C., and then heat-set to produce a separator.
[0082] Comparative Example 6 A separator was manufactured as follows according to the method of FIG. 4. A first composition, which was a mixture of 28 parts by weight of high density polyethylene (HDPE) having a weight average molecular weight of 600,000 and 72 parts by weight of paraffin oil having a kinetic viscosity of 70 cSt at 40°C, was fed into a twin-screw extruder (first extruder, inner diameter 58 mm, L / D=56). The first extruder was extruded through a T-die having a width of 400 mm under conditions of a screw rotation speed of 120 rpm and a temperature of 210°C, and then passed through a casting roll at a temperature of 70°C to manufacture a first sheet having a thickness of 800 μm.
[0083] The second composition, which was the same as the first composition, was fed into a twin-screw extruder (second extruder, inner diameter 58 mm, L / D=56) that had the same configuration as the first extruder and was arranged in parallel. The second composition was extruded from a T-die with a width of 400 mm under conditions of a screw rotation speed of 120 rpm and a temperature of 210° C., and then passed through a casting roll at a temperature of 70° C. to produce a second sheet with a thickness of 800 μm.
[0084] The first and second sheets were fed into a laminator installed downstream of the first and second extruders, and the first and second sheets were laminated together to obtain a laminate. The laminate was fed into a stretching machine (roll stretching machine) and stretched 8 times in the machine direction (MD) at 120°C to produce a precursor film. The precursor film was fed into a tenter stretching machine and stretched 9 times in the transverse direction (TD) at 126°C, and then immersed in a dichloromethane leaching tank at 25°C for 1 minute to extract and remove paraffin oil, and then dried at 38°C for 5 minutes. The laminate was stretched 1.5 times in the transverse direction (TD) at 138°C, and then relaxed 10% and heat-set to obtain a separator.
[0085] Experimental Example 1 Each of the separators produced in the Examples and Comparative Examples was cut to 100 mm x 100 mm, and the cut separator test pieces were then divided into 5 equal parts in the machine direction (MD) to obtain test pieces 1 to 5 of 20 mm x 100 mm (MD x TD).
[0086] The cross section of each specimen was photographed using SEM, and the thickness (μm) of the outermost layer was measured at the center of the transverse direction (TD) of each specimen. Based on this, the thickness deviation defined by the following formula was calculated and shown in Table 1 below. <expression> Thickness deviation (%) = {(maximum thickness) - (minimum thickness)} / (minimum thickness) x 100
[0087] In the cases of Examples 1 to 8 and Comparative Example 6, a layer derived from the first composition was selected as the outermost layer, and in the cases of Comparative Examples 1 and 5, a layer derived from the first polyolefin solution was selected as the outermost layer. The separators according to Comparative Examples 2 to 4 had a single-layer structure, and were therefore excluded from the measurement targets.
[0088] [Table 1]
[0089] Experimental Example 2 The thickness, puncture strength, tensile strength and tensile elongation of the separators prepared in the examples and comparative examples were measured as follows. Unless otherwise specified for temperature, the measurements were performed at room temperature (25°C), and the results are shown in Table 2 below.
[0090] - Thickness (μm): The thickness of the support test piece was measured using a micro thickness measuring device. - Puncture strength (gf): Using a puncture strength tester, force was applied with a stick to a separator test piece measuring 100 mm x 50 mm until the sample was punctured, and the force applied was measured.
[0091] - Tensile strength (kgf / cm 2 ): Using a tensile strength tester, the stress applied to a separator test piece measuring 20 mm x 200 mm in the machine direction (MD) and transverse direction (TD) until fracture occurred was measured.
[0092] -Tensile elongation (%): Using a tensile strength tester, the percentage of elongation of a separator specimen measuring 20 mm x 200 mm in length in the machine direction (MD) and transverse direction (TD) until breakage occurred was measured.
[0093] [Table 2]
[0094] The above description of the present invention is for illustrative purposes only, and those skilled in the art will understand that the present invention can be easily modified in other specific forms without changing the technical idea or essential features of the present invention. Therefore, the above-described embodiments should be understood to be illustrative in all respects and not restrictive. For example, each component described as a single type may be implemented in a distributed form, and similarly, each component described as a distributed type may be implemented in a combined form.
[0095] The scope of the present invention is defined by the claims set forth below, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be understood to be included within the scope of the present invention.
Claims
1. (a) extruding a first composition comprising a first polyolefin and a first pore former to produce a first sheet; (b) extruding a second composition comprising a second polyolefin and a second pore former to produce a second sheet; (c) stretching the first and second sheets in a machine direction (MD) to produce first and second precursor films; (d) laminating the first and second precursor films to obtain a laminate; and (e) removing the first and second pore formers from the laminate after stretching the laminate in the transverse direction (TD).
2. 2. The method for producing a multi-layer separator according to claim 1, wherein the first and second polyolefins each comprise one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, and combinations or copolymers of two or more thereof.
3. 3. The method for producing a multi-layer separator according to claim 2, wherein the weight average molecular weight of each of the first and second polyolefins is 300,000 to 2,000,000.
4. 2. The method of claim 1, wherein the first and second pore-forming agents are each paraffin oil having a kinematic viscosity at 40° C. of 50 to 100 cSt.
5. The method for producing a multi-layer separator according to claim 1 , wherein the first or second composition further comprises a hydrophilic polymer.
6. 6. The method for producing a multilayer separator according to claim 5, wherein the content of the hydrophilic polymer in the first or second composition is 0.1 to 5% by weight.
7. 7. The method for producing a multilayer separator according to claim 6, wherein the hydrophilic polymer is one selected from the group consisting of ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl alcohol, polyacrylic acid, polyoxyethylene-polyoxypropylene block copolymers, polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone, polyvinyl acetal, polyvinyl butyral, cellulose derivatives, glycerol, and combinations of two or more thereof.
8. 2. The method for producing a multilayer separator according to claim 1, wherein the first and second precursor films are pressed against each other during the lamination, so that at least a portion of the interface between the first and second precursor films is adhered to each other.
9. A multi-layer separator manufactured by the manufacturing method according to any one of claims 1 to 8, A multi-layer separator having an outermost layer having a thickness deviation of 10% or less as measured by the following formula: <Formula> Thickness deviation (%) = {(maximum thickness) - (minimum thickness)} / (minimum thickness) x 100 In the above formula, the thickness deviation is determined by a method including the steps of: cutting the multilayer separator to 100 mm x 100 mm (MD x TD), then dividing it into 5 equal parts in the machine direction (MD) to obtain 5 test pieces each having a size of 20 mm x 100 mm (MD x TD); measuring the thickness of the outermost layer at the center of the test pieces in the machine direction (TD); and calculating the thickness deviation using the formula based on the maximum and minimum thickness values.
10. The multi-layer separator of claim 9, wherein the multi-layer separator satisfies at least one of the following conditions (i) to (vi): (i) a thickness of 1 to 15 μm; (ii) Puncture strength of 600 gf or more, (iii) Machine direction (MD) tensile strength: 1,300 to 2,000 kgf / cm 2 , (iv) Transverse (TD) tensile strength: 3,000 to 6,000 kgf / cm 2 , (v) a machine direction (MD) tensile elongation of 150-450%, and (vi) Transverse direction (TD) tensile elongation of 30-100%.
Citation Information
Patent Citations
Opaque laminated drawn molding with pearllike luster and preparation thereof
JP1991110149A
Wide microporous film
JP2023526644A
Preparation method of a multi-layer complex separator, multi-layer complex separator formed therefrom and electrochemical device including the same
KR1020140144584A
Separator film for Lithium ion battery with high toughness and heat shrinking and its manufacturing method
KR1020180024101A
Wide microporous film
WO2021236573A1